Efficiency of Zakat Fund Payment through "E-Muzakki" in Industrial Revolution 4.0 - Indah Maesaroh; Anisa Nurul Fauziyah; Ishak Ishak (Journal of Islamic Economic Scholar, 2021)
Indonesia is one of the countries with the most Muslim population in the world. Around 80% of the total population of Indonesia is Muslim. So it is not surprising, that Islam and various kinds of Islam exist in Indonesia. Apart from that, Islam there is known as Islam which is quite advanced and developing as well as being very tolerant of other religions whose numbers are also not small. In this case, Indonesia is indeed not an Islamic state, but it does not rule out the possibility that zakat in Indonesia can be far more developed than other countries. Zakat certainly has a very important role for the economy in Indonesia, this is certainly also supported by the majority Muslim population in Indonesia. In writing this paper, the author uses the type of library research, in which problems are described based on data contained in literature or documents. Then analyzed further to be drawn a conclusion. it can be concluded that related to this research is the concept of zakat fund payment theory can be applied as a platform to make zakat payments effectively and efficiently for millennials. E-Muzakki is a platform or application that makes it easy for muzakki who have funds to reach their nishob to pay zakat.